Implementation of the Code of Ethics in Improving the Professionalism of Christian Religious Education Teachers - Joko Prihanto; Victor Deak; Yohanan Linugroho (Formosa Journal of Multidisciplinary Research, 2023)
This scientific work discusses the importance of implementing a teacher's code of ethics in increasing the professionalism of Christian religious education teachers in schools. The teacher's code of ethics is a rule or guideline that regulates the behavior of teachers in carrying out their duties as educators. In this scientific work, the authors found that implementing a teacher's code of ethics can help increase awareness of teacher responsibilities as educators, increase public trust in the teaching profession, and help build good relationships between teachers, students, and parents. Support is needed from all parties, such as schools, government, and society to ensure the implementation of the teacher's code of ethics is carried out properly and sustainably. This scientific work confirms that the implementation of the teacher's code of ethics is very important in increasing the professionalism of Christian religious education teachers in schools.